Влияние рецепторного антагониста интерлейкина-1 на динамику показателей системы глутатиона, энергетического метаболизма и окислительной модификации белков при экспериментальной гипергликемии - Супрун, А. С.; Беленичев, И. Ф.; Suprun, A. S.; Belenichev, I. F.; Бєленічев, Ігор Федорович (My University, 2014)
Aim. To study the dynamics of glutathione system, energy metabolism and the oxidative protein modification indicators in rat brain tissue in case of experimental diabetes mellitus and use of metabolic action cerebroprotector Piracetam + Thiotriazoline (Tiocetam) and cytokine medication — recombinant interleukin-1 receptor antagonist. Methods. Studies were conducted on 40 white Wistar rats, divided into four groups of 10 animals each. First group — intact animals, second — animals with experimental diabetes mellitus, the third — animals with diabetes mellitus treated with Piracetam + Thiotriazoline (Tiocetam) administered at a dose of 500 mg/kg, the fourth — animals with diabetes mellitus treated with recombinant interleukin-1 receptor antagonist at a dose of 7.5 mg/kg. Experimental diabetes mellitus was induced by injection of an aqueous solution of alloxan monohydrate. Blood glucose concentration was measured on the 11th day after alloxan injection. Brain tissue specimens were used for biochemical studies. Statistical data analysis was performed using the Statistica 6.0 software package, the comparative analysis in the groups was performed using ANOVA. Results. The development of hyperglycemia in experimental animals was accompanied with glutathione system destabilization (increased levels of oxidized glutathione along with a marked decrease in its reduced form, glutathione peroxidase and glutathione reductase activity). Ischemic lesion of the brain tissue of animals with experimental diabetes mellitus was characterized with an increase of markers of oxidative protein modification (aldehyde and carboxyl products) and energy deficit in brain homogenate. Treatment with Piracetam + Thiotriazoline (Tiocetam) and interleukin-1 receptor antagonist contributed to the normalization of the glutathione peroxidase and glutathione reductase activity, stabilization of energy phosphates and indicators of oxidative protein modification. Maximal activity was observed in case of interleukin-1 receptor antagonist. Conclusion. The activity of the interleukin-1 receptor antagonist in terms of glutathione system stabilization and inhibition of oxidative and nitrozilizing stress manifestations exceeds those of Piracetam + Thiotriazoline (Tiocetam).
Influence of interleukin-1 receptor antagonist on dynamics of the glutathione system, energy metabolism and oxydative protein modification in experimental hyperglycemia
Keywords: interleukin-1 receptor antagonist; experimental diabetes mellitus; alloxan; glutathione; Tiocetam